Screening for subclinical inflammation in ejaculates - Eggert-Kruse, Waltraud; Probst, Stephan M.; Rohr, Gerhard; Aufenanger, Johannes; Runnebaum, Benno (Fertility and sterility, 1995)
Objective - To determine the clinical significance of albumin determination in ejaculates by means of an easy office test to screen semen samples for subclinical infection-inflammation. - Patients - One hundred fifty-nine randomly chosen males of couples with longstanding infertility (median duration of infertility 4 years (range 1 to 19 years) without clinical signs or symptoms of genital tract infection. - Setting - Outpatient Infertility Clinic of the University of Heidelberg, Germany. - Main Outcome Measures - Screening of ejaculates for subclinical infection-inflammation by means of a ready-to-use kit for semiquantitative detection of albumin in addition to determination of leukocytes rates by means of monoclonal antibodies for differentiation of round cells and measurement of granulocyte elastase concentration in semen samples. Evaluation of sperm quality by means of standard sperm analysis including determination of local antisperm antibodies with the mixed antiglobulin reaction, evaluation of sperm functional capacity in vitro with the standardized sperm-cervical mucus (CM) penetration test, and semen cultures. All tests were performed from aliquots of the same ejaculates. - Results - Screening of semen samples for elevated albumin with the modified paper strips proved to be very easy, quick, and suitable for routine use. Positive results were not related markedly to medical history and outcome of clinical examination as well as to standard parameters of sperm analysis and were not influenced by local antisperm antibodies of the immunoglobulin (Ig)G and/or IgA class and microbial colonization. However, albumin-positive semen samples were significantly less frequent in case of very good outcome of the sperm-CM penetration test. A significant relationship was found with high rates of leukocytes of the round cells in semen samples (total range 0% to 96%) and the concentration of granulocyte elastase (total range 1 to 880 μg/L). - Conclusions - The results of this prospective study suggest that the determination of albumin in semen samples with ready-to-use test kits might be a valuable additional marker for subclinical infection-inflammation of the male genital tract and therefore suitable for screening during infertility investigation.
Elektronische Reproduktion der Druck-Ausgabe 26. April 2016
Gesehen am 21.11.2024